Diálogo en acción. Material didáctico para el fortalecimiento de la expresión y la argumentación oral en estudiantes de grado undécimo (2024)
This degree project presents the planning, design, and evaluation of “Diálogo en acción”, a didactic material aimed at strengthening discursive and argumentative skills in eleventh-grade students at Colegio Colombo Bilingüe Florida. This resource arises in response to the identified need to improve oral expression within the Colombian educational context, emphasizing the importance of implementing effective strategies that promote critical thinking and respectful argumentation. Following a structured and visually appealing approach, “Diálogo en acción” consists of thematic cards that facilitate the organization of debates, allowing students to articulate their opinions and connect disciplinary content with transversal skills necessary for their academic and social development. The document details the construction process of the material, its validation by experts, and evaluates how this resource can significantly contribute to the development of oral expression and critical analysis in students of language and literature.